Effect on ovarian weight of female albino rat with histological changes after prolonged ovulation induction - Fauzia Qureshi, Mohtasham Hina, Maria Tasleem, Fatima Inam, Shumaela Kanwal, Ayesha Imtiaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Infertility is becoming global health issue, which affects multiple aspects of human life in both genders . Medical induction of ovulation with clomiphene citrate has been first line of treatment of infertility since 1962 . Discrepancy in ovulation rate and pregnancy rate with clomiphene citrate along with multiple complication in most of the infertile patients raises the question for alternative treatment . Increased risk of (OHSS) ovarian hyperstimulation syndrome is associated with prolonged ovulation induction. Letrozole was found to be an effective alternative ovulogen. Aim: To study the effects on ovarian weight of female albino rat with histological changes after ovulation induction with letrozole and clomiphene citrate . Method: An experimental study was conducted at animal house of PGMI with 84 female Wistar albino rats having weight between 150-250gm.The study was carried out after approved by Ethical Committee of Postgraduate Medical Institute, Lahore. Eighty four rats were equally divided into three groups (one control group A and two experimental groups B & C). Normal saline was given orally to the group A , letrozole(Femara) at dose 5mg/kg and clomiphene citrate at dose 100ug/kg were given orally to B & C groups respectively . Major groups were further subdivided into four subgroups according to duration of treatment (1-4 estrous cycle ). Ovaries of female albino rats were removed after dissection and weight was calculated. Ovarian sections were made and stained with Haematoxylin and Eosin, to study the histology of ovaries. Results: Experimental study showed statistically significant difference in the weight of ovary among control and experimental groups after 1-4 estrous cycles but insignificant difference was observed between letrozole and clomiphene citrate group. This showed that both drugs have enhanced the folliculogenesis as increase in ovarian weight is due to enhanced gonadotropic activity . Normal histological features were observed with letrozole even after 4 estrous cycle. But in clomiphene citrate group after 4 estrous cycles, significant increase in ovarian weight with cystic follicles arrangement at the periphery of ovary showing Practical implication: As ovary is an important reproductive & endocrine organ and plays vital role in female reproductive life , this study showed the hazardous effects of commonly used clomiphene medicine on ovary . Practically letrozole should be used as first line of treatment as it is safe &does not damage the normal histology of ovary . Conclusion: Present study concluded that there is increase in ovarian weight after ovulation induction with Letrozole and clomiphene citrate. But Significant increase in ovarian weight along with cystic changes in ovarian histology with Clomiphene citrate after prolonged use might be hallmark of OHSS (Ovarian hyper stimulation syndrome), still lots of work is required in this regard. Keywords: Ovarian weight, Clomiphene citrate, letrozole, OHSS, Cystic follicles .